Pengaruh Citra Merek dan Kepercayaan Terhadap Keputusan Pembelian Sandal Manik Bybuca @bybuca.id - Bella Charisma Sasmita; Nur Hayati (CV. Ulil Albab Corp, 2024)
Abstract: Bybuca comes by offering a combination of trendy style and high quality in their footwear products. Their latest innovation, the “beads sandal”, combines attractive style with comfort and functionality, designed based on consumer preferences and global trends. The purpose of this research is to find out how brand reputation and consumer trust in Bybuca brand Manic Sandals influence their decision to buy this product. This research uses a purposive sampling method by distributing questionnaires to Bybuca customers via Instagram social media. The results of this study show that brand image and trust together have a significant positive effect. The trust variable influences purchasing decisions, but the brand image variable does not partially influence it.